Methods of estimation of risk of innovative projects - Eskendyr, E. E. (Journal of Economic Research & Business Administration, 2015)
Talk of driving riskiness article, decrease riskiness and considering ways to appreciate the innovative project. In our country, a new long-term strategic plan in 2050 and the industry has put innovation at center stage. Kazakhstan is interested in the future to further develop economic cooperation countries. Therefore, to achieve the maximum benefit of economic riskiness innovate for the main tives. To minimize the riskiness of he innovative project considered several periods. The project is the most benefi cial exercise through those periods, profi table activities in the state of threat-risk considered. Appreciate numerical and qualitative methods of risk fully shown. Innovative project riskiness high and uses its versatile study and evaluation activities. Duration related payback discount embroider vzavisomosti time and its vyshivatovanie algoritomnym study.